2011
DOI: 10.1016/j.atherosclerosis.2011.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Higher cystatin C level predicts long-term mortality in patients with peripheral arterial disease

Abstract: Aims-Cystatin C and cathepsins could play a role in different processes and stages of the atherosclerotic disease. We aimed to investigate the relationship of cystatin C, and cathepsins L, and S, to lethal outcome in patients with peripheral arterial disease (PAD).Methods and results-We studied 378 patients with established PAD. Cox regression was used to assess relationships between serum cystatin C or cathepsins L and S, and time to lethal outcome. The role of cystatin for prognosis of cardiovascular death w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
37
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 36 publications
6
37
2
1
Order By: Relevance
“…However, we propose that two potential mechanisms might be responsible for the association of cystatin C with no-reflow after PPCI. First, cystatin C has been implicated in the local and systemic inflammatory response, and high cystatin C levels have been found to be strongly associated with high concentrations of CRP [22][23][24]. In the present study, we also found a significant positive correlation between high cystatin C levels and increased hs-CRP concentrations.…”
Section: Serum Cystatin C Levels and Impaired Microvascular Perfusionsupporting
confidence: 77%
“…However, we propose that two potential mechanisms might be responsible for the association of cystatin C with no-reflow after PPCI. First, cystatin C has been implicated in the local and systemic inflammatory response, and high cystatin C levels have been found to be strongly associated with high concentrations of CRP [22][23][24]. In the present study, we also found a significant positive correlation between high cystatin C levels and increased hs-CRP concentrations.…”
Section: Serum Cystatin C Levels and Impaired Microvascular Perfusionsupporting
confidence: 77%
“…18,39,40 Previously it has been shown that serum cystatin C is associated better with mortality than creatinine and estimated GFR based on creatinine in eldery, 26 in patients with coronary heart disease, 41 heart failure, 42 and also in patients with peripheral arterial disease. 43 Serum cystatin C was a strong and independent predictor of mortality also in patients with normal to moderately impaired renal function. 42,44,45 In these studies, GFR was estimated by using less accurate CockcroftGault or MDRD Study equations.…”
Section: Discussionmentioning
confidence: 99%
“…18 One study reported that higher CysC levels independently predicted 5 y all-cause and cardiovascular death in subjects with peripheral arterial disease. 19 A positive correlation between CysC and inflammatory parameters, including interleukin-6, resistin, tumor necrosis factor, and C-reactive protein, has been reported. 20 Fig .…”
Section: Discussionmentioning
confidence: 99%